Взаємодія лецитину з поверхнею високодисперсних оксидів - Аndriyko, L. S.; Маlysheva, M. L.; Zarko, V. I.; Gun'ko, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2011)
Adsorption of lecithin onto a surface of highly disperse oxides was investigated. The degree of interaction of adsorbate molecules with silanol groups of fumed oxide surface was estimated using IR spectroscopy. Irreversible adsorption of lecithin on the surface of fumed oxides (in amount corresponding to monolayer capacity) was elucidated by means of thermogravimetry. It was found that the adsorption of lecithin onto fumed oxide surface caused changes in cluster formation of water molecules at the interfaces of fumed oxides–water. According to the thermally stimulated depolarization (TSD) data, this process is influenced by the nature of adsorbate. Adsorbed lecithin promotes the formation of the same water clusters as in pure 3% lecithin solution with a low number of the hydrogen bonds (»2), Tmaх = 120 K and nanodomains of bulk water (»4, T = 200…220 K). It was shown that the surface charge density of fumed silica (σA–300) is changed by lecithin adsorption over the range from pH 3 to 10 and the surface acquires the negative charge. But at pH > 9 σA–300/lecithin it is significantly smaller than σA–300.